In silico-based Discovery of New Potential Drugs Targeting Severe Acute Respiratory Syndrome Coronavirus 2 Spike Glycoprotein - Hayam Abdelkader; Mahmoud Rifaat; Mohammed Baghdadi; Nariman Sindi; Radwa Rifaat (Dr. Sulaiman Al Habib Medical Journal)
The SARS-CoV-2-induced novel coronavirus disease has become a global pandemic. As the latest coronavirus variants are even more infectious and deadly, its treatment is very difficult. Currently used drugs such as remdesivir, saquinavir, and chloroquine have several drawbacks. Recent studies have reported key proteins that could serve as drug targets. Amongst them, the spike (S) glycoprotein is an attractive drug target that plays a prominent role in viral binding and entry. With the aim of targeting and blocking the S protein, we designed a computational study for screening novel antiviral compounds. Molecular docking was used as a screening tool, and Molecular Dynamics (MD) simulations were used to further confirm the stability of ligand-bound complexes. The Asinex antiviral database was screened using a recently resolved S protein (PDB ID: 7C2L). The Schrodinger software suite was used for preparing the protein and ligand structures prior to performing the docking experiment. Based on the docking scores, antiviral compounds were screened and the docked complexes of top-performing hits were tested for complex stability and presence of molecular interactions using MD simulations. Finally, based on the nature of molecular interactions, six prospective hits– LAS 51389346, BDH 33920970, LAS 51389268, LAS 51389282, LAS 51389262, and LAS 51389430–were screened. Among these compounds, LAS 51389268, BDH 33920970, and LAS 51389268 showed consistent and strong binding with S glycoprotein, predicting them as prospective candidates for COVID-19 treatment. In conclusion, this study screened out novel prospective antiviral compounds that can intervene with virion entrance thereby being of potential use to treat COVID-19.